2019
DOI: 10.1007/s00380-019-01475-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between left atrial reverse remodeling and maintenance of sinus rhythm after catheter ablation of persistent atrial fibrillation

Abstract: The success rate of catheter ablation of persistent atrial fibrillation (AF) is not satisfactory, for reasons that are unclear. The purpose of this study was to examine the relationship between left atrial reverse remodeling after ablation and recurrence of AF in patients with persistent AF. One hundred and thirty-two patients with persistent AF were enrolled. Extensive encircling pulmonary vein isolation plus ablation of complex fractionated atrial electrograms was performed. Bepridil or amiodarone was prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
1
20
0
3
Order By: Relevance
“…For example, the left atrial dimensions at three months (44 ± 6 versus 40 ± 6 mm, p < 0.001) and six months (44 ± 6 versus 40 ± 6 mm, p < 0.001) were significantly smaller compared with just after ablation in the patients without AF recurrence. Additionally, the authors found a significant decrease of the natriuretic peptide concentrations between baseline levels and those at three and six months (111.0 versus 34.9 pg/mL, p < 0.001; 111.0 versus 30.4 pg/mL, p < 0.001), thus furtherly confirming the potential benefits of catheter ablation not just for AF management, but also for the outcome of patients with ACM and HF [ 71 ].…”
Section: Particular Therapeutic Approachesmentioning
confidence: 84%
“…For example, the left atrial dimensions at three months (44 ± 6 versus 40 ± 6 mm, p < 0.001) and six months (44 ± 6 versus 40 ± 6 mm, p < 0.001) were significantly smaller compared with just after ablation in the patients without AF recurrence. Additionally, the authors found a significant decrease of the natriuretic peptide concentrations between baseline levels and those at three and six months (111.0 versus 34.9 pg/mL, p < 0.001; 111.0 versus 30.4 pg/mL, p < 0.001), thus furtherly confirming the potential benefits of catheter ablation not just for AF management, but also for the outcome of patients with ACM and HF [ 71 ].…”
Section: Particular Therapeutic Approachesmentioning
confidence: 84%
“…Since the establishment of PVI due to advances in catheter technologies and techniques, numerous studies have demonstrated LA reverse remodeling due to restoration and maintenance of sinus rhythm after PVI 9‐20, 27‐31 . Regarding LA structural reverse remodeling, meta‐analyses revealed that LA diameter and LA volume were significantly decreased by AF ablation 18, 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the establishment of PVI due to advances in catheter technologies and techniques, numerous studies have demonstrated LA reverse remodeling due to restoration and maintenance of sinus rhythm after PVI. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 27 , 28 , 29 , 30 , 31 Regarding LA structural reverse remodeling, meta‐analyses revealed that LA diameter and LA volume were significantly decreased by AF ablation. 18 , 19 On the other hand, although the LA function was also improved by successful RFCA, several studies have reported persistent LA functional abnormalities after effective ablation.…”
Section: Discussionmentioning
confidence: 99%
“…LAD reduction was calculated as (LAD during index hospitalization-LAD at follow-up echocardiography)/ LAD during index hospitalization × 100 (%). LA reverse remodeling was defined as LAD reduction ≥ 5% at follow-up echocardiography 18 . Patients were classified according to LVEF at index hospitalization (HFpEF: LVEF ≥ 50%, HFmrEF: LVEF 40%–49% and HFrEF: LVEF < 40%).…”
Section: Methodsmentioning
confidence: 99%